Synchronized Skating in Canada: Historical and Ethnographic Perspectives - Hall, Leslie (MUSICultures, 2013)
Figure skating is an interdisciplinary activity, going beyond athletics and involving choreography, music, creativity, spectacle and interpretation. This ethnographic study focuses on a transnational figure skating genre called synchronized skating, performed mainly by girls and young women on teams consisting of ten to twenty skaters. Drawing on historical and ethnographic perspectives, the author examines local and national practices with an emphasis on how synchronized skating embodies musical, social and political synergies.